Ubiquitous computing and ambient intelligence. 10th International Conference, UCAmI 2016, San Bartolomé de Tirajana, Gran Canaria, Spain, November 29-December 2, 2016, Proceedings /: 10th International Conference, UCAmI 2016, San Bartolomé de Tirajana, Gran Canaria, Spain, November 29-December 2, 2016, Proceedings. Part II : (2016) - Unknown
No abstract available